The Dynamics of Foreign Direct Investments in Central and Eastern Europe Under the Impact of International Crisis of 2007 - Anca Elena Nucu (CES Working Papers, 2011)
As an engine for economic development of CEE countries, FDI inflows have contributed to creating new jobs and access to modern technologies; have had positive effects on balance of payments and state budget revenues. The purpose of this article is to highlight the implications of international financial and economic crisis of 2007 on FDI in CEE countries. Also, we realized a comparative approach of the factors that influence investors' decisions in Czech Republic, Hungary, Poland, Romania, Slovakia and a SWOT analysis of FDI in Romania at the end of 2009. The second part of the article represents an econometric analysis using SPSS of FDI impact on GDP and unemployment rate on the example of Romanian economy during 1991-2009. The fundamental hypothesis of econometric analysis is the following: it is a direct link between FDI and GDP, respectively, an inverse link between FDI and unemployment rate.
Keywords: 330; FDI; unemployment rate; GDP; financial crisis; CEE countries